Does diversification improve the performance of German banks? Evidence from individual bank loan portfolios - Natalja von Westernhagen; Daniel Porath; Evelyn Hayden (Deutsche Bundesbank, 2006)
Should banks be diversified or focused? Does diversification indeed lead to enhanced performance and, therefore, greater safety for banks, as traditional portfolio and banking theory would suggest? This paper investigates the link between banks? profitability (ROA) and their portfolio diversification across different industries, broader economic sectors and geographical regions measured by the Herfindahl Index. To explore this issue, we use a unique data set of the individual bank loan portfolios of 983 German banks for the period from 1996 to 2002. The overall evidence we provide shows that there are no large performance benefits associated with diversification since each type of diversification tends to reduce the banks? returns. Moreover, we find that the impact of diversification depends strongly on the risk level. However, it is only for moderate risk levels and in the case of industrial diversification that diversification significantly improves the banks? returns.
Keywords: G21; G28; G32; 330; focus; diversification; monitoring; bank returns; bank risk; Bank; Kreditgeschäft; Diversifikation; Portfolio-Management; Deutschland